Palaro a play therapy center for children in trauma - Tapia, Reeza Mei B. (College of Architecture, University of the Philippines Diliman, 2019)
Play is the child's medium of expression. It is an essential part to the child's development. Because children are among the vulnerable age group, they are prone to being victims of abuse and violence. Children are constantly faced with abandonment, grief, and fear. Studies show that other forms of abuse towards children are also increasing, adding up to the pressing issue that children's rights are still constantly violated (Roche, 2017). These violence and abuse cause detrimental effect to their development, impairing their cognitive functioning. Thus, being aware of their mental health is a rational step towards fighting for their human rights. This project used an unconventional approach towards therapy which blends recreation or "play" in the treatment of trauma among children. Play therapy deviates from intimidating psychological treatments, helping eliminate the stigma on availing mental health services.